(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In this article, the artistic plot and types of conflict, the uniqueness of dramatic interpretation in the story of the writer S.Moem’s "Chadiqli kishi" were studied. This story is one of the unique aspects of S.Maugham’s artistic thinking, and it shows the growing human kindness in society.